(untitled) (Window of Midwifery Journal, 2026)
Anemia is a condition characterized by a lower-than-usual hemoglobin level in the blood. The purpose of this study was to analyze the relationship between the level of knowledge, menstrual disorders, and body mass index and the incidence of anemia in female adolescents in high schools within the working area of the Marina Permai Palangka Raya Health Center, using an analytical observational method with a cross-sectional approach. The research sample consisted of 108 female adolescents from high schools within the working area of the Marina Permai Palangka Raya Health Center. Sampling was done using proportional random sampling. Data analysis employed descriptive statistics, chi-square tests, and multiple logistic regression. The results of the chi-square analysis showed a p-value for the variable level of knowledge (p = 0.375), menstrual disorders (p = 0.001), and body mass index (p = 0.000). The results of the multiple logistic regression analysis showed a p-value and Exp(B) for the variable menstrual disorders (p = 0.000, Exp(B) = 20.300) and body mass index (p = 0.000, Exp(B) = 25.477). There is a relationship between menstrual disorders and body mass index with the incidence of anemia in female adolescents. There is no relationship between knowledge level and the incidence of anemia in adolescent girls. The most dominant variable associated with the incidence of anemia in adolescent girls is body mass index